PERFORMANCE-ORIENTED DESIGN OF A DUAL-ROTOR AXIAL-FLUX FLUX-REVERSAL MACHINE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This study presents a dual-rotor axial-flux flux-reversal permanent magnet machine (DR-AFFRM) topology, combining a dual-rotor and axial-flux configuration that is not widely documented in the literature. The proposed design innovatively combines an axial-flux configuration with a dual-rotor architecture to enhance torque density while mitigating torque ripple. A finite element model integrated with a genetic algorithm-based optimization framework is employed to optimize critical geometric and magnetic parameters. The optimized design reduces permanent magnet volume by 53.48%, improves efficiency from 81.62% to 84.11%, and delivers an average torque of 106.44 Nm at 1500 rpm. The linear torque–current characteristic confirms effective magnetic utilization without saturation. The results demonstrate that the proposed topology provides a balanced, high-performance solution for high-precision electric-drive applications.
Keywords: Dual-rotor machine; Axial-flux machine; Torque ripple; Optimization; Finite element analysis (FEA)